The Effect of Concomitant Arthroscopic Lateral Retinacular Release on Postoperative Patellar Position and Orientation in Open Wedge High Tibial Osteotomy - Murayama, Kazuhiro (Knee Surg Relat Res, 2018)
PURPOSE: The purpose of this study was to evaluate the effect of concomitant arthroscopic lateral release (LR) in open wedge high tibial osteotomy (OWHTO) by comparing the pre- and postoperative radiological parameters of patellar position and orientation. MATERIALS AND METHODS: The study was comprised of 19 knees undergoing OWHTO and concomitant LR and 18 knees undergoing OWHTO alone. Radiological parameters for patellar position and orientation included the Caton-Deschamps index (CDI), Blackburne-Peel index (BPI), patellar tilting angle (PTA), patellar lateral shift (PLS), and patellofemoral distance (PFD), which were evaluated in the preoperative period and at one year after surgery. RESULTS: Patellar height was significantly reduced after surgery as indicated by the decrease in BPI (p=0.03) in the OWHTO/LR group, and decrease in CDI (p=0.03) and BPI (p=0.04) in the OWHTO alone group. PTA and PLS were significantly reduced after the combined OWHTO/LR procedure (p=0.04 and p=0.04, respectively). By contrast, no significant changes were detected when isolated OWHTO was performed. CONCLUSIONS: OWHTO induced a postoperative decrease in patellar height in both groups. Regarding the change in patellofemoral alignment, concomitant LR in OWHTO significantly decreased lateral patellar tilt and shift, while no significant difference in those parameters were noted in the OWHTO alone knees.